Fluid intelligence loss linked to restricted regions of damage within frontal and parietal cortex. - Woolgar, A; Parr, A; Cusack, R; Thompson, R; Nimmo-Smith, I; Torralva, T; Roca, M; Antoun, N; Manes, F; Duncan, J (2010)
Tests of fluid intelligence predict success in a wide range of cognitive activities. Much uncertainty has surrounded brain lesions producing deficits in these tests, with standard group comparisons delivering no clear result. Based on findings from functional imaging, we propose that the uncertainty of lesion data may arise from the specificity and complexity of the relevant neural circuit. Fluid intelligence tests give a characteristic pattern of activity in posterolateral frontal, dorsomedial frontal, and midparietal cortex. To test the causal role of these regions, we examined fluid intelligence in 80 patients with focal cortical lesions. Damage to each of the proposed regions predicted fluid intelligence loss, whereas damage outside these regions was not predictive. The results suggest that coarse group comparisons (e.g., frontal vs. posterior) cannot show the neural underpinnings of fluid intelligence tests. Instead, deficits reflect the extent of damage to a restricted but complex brain circuit comprising specific regions within both frontal and posterior cortex.